Skin Bleaching Among African and Afro-Caribbean Women in New York City: Primary Findings from a P30 Pilot Study - Emma K. T. Benn; Richa Deshpande; Ogonnaya Dotson-Newman; Sharon Gordon; Marian Scott; Chitra Amarasiriwardena; Ikhlas A. Khan; Yan-Hong Wang; Andrew Alexis; Bridget Kaufman; Hector Moran; Chi Wen; et al. (Dermatology and Therapy, 2019)
Abstract Introduction The application of skin bleaching products to inhibit melanogenesis is a common practice within the African diaspora. Despite the adverse health effects of skin bleaching, rigorous studies investigating skin bleaching behavior among these populations in the United States are limited. In our P30 pilot study, we explored predictors of skin bleaching practice intensity among African and Afro-Caribbean women. Methods In collaboration with our Community Engagement Core, we conducted a cross-sectional study to investigate the relationship between demographic and psychosocial predictors and skin-bleaching-related practice patterns among African and Afro-Caribbean women in New York City. Results Among the 76 participants recruited, the median age at the initiation of skin bleaching was 19.5 (16–25) years, yielding a median duration of 13.5 (6–23) years. Although pregnant women were not actively recruited for the study, 13.2% (n = 10) of the participants used skin bleaching products while pregnant or possibly breastfeeding. Nativeness and education were associated with various components of skin bleaching practice intensity, including duration of skin bleaching, daily use of products, and bleaching of the entire body. Participants’ perceived skin-color-related quality of life was not associated with skin bleaching practice intensity. Conclusion Skin bleaching is a habitual practice that likely requires culturally sensitive interventions to promote behavioral change. The existence of prenatal and postnatal exposure to mercury, hydroquinone, and other potentially harmful chemicals in skin bleaching products highlights an urgent need to explore the adverse effects of skin bleaching practices on birth outcomes and the growth and neurodevelopment of young babies.